Body Fatness and Markers of Thyroid Function among U.S. Men and Women - Kitahara, Cari M.; Platz, Elizabeth A.; Ladenson, Paul W.; Mondul, Alison M.; Menke, Andy; de González, Amy Berrington (PLOS ONE, 2012)
Background We evaluated the association of central versus overall adiposity on levels of thyroid stimulating hormone (TSH), free triiodothyronine (fT3), and free thyroxine (fT4) among euthyroid subjects taken from a cross-sectional, representative sample of the adult non-institutionalized U.S. population. Methods The National Health and Nutrition Examination Survey 2007–2008 included 1,623 men and 1,491 women who were 20 years and older, with no history of thyroid or liver disease, kidney failure, diabetes, or thyroid function-altering prescription medication use (based on self-report), and having TSH, fT3, and fT4 levels between 0.5–4.49 mIU/L, 2.5–3.9 pg/mL, and 0.6–1.6 ng/dL, respectively. Associations between body mass index (BMI) and waist circumference (measures of overall and central adiposity, respectively) and TSH, fT3, and fT4 levels were estimated using multivariable linear regression models stratified by sex and adjusted for age, race, smoking status, and alcohol intake. Results An increase in serum TSH levels was observed for every 1-quartile increase in BMI in euthyroid men (3.8% [95% CI 0.8%, 6.8%]) and euthyroid women (4.0% [95% CI 1.6%, 6.5%]). Similar, albeit slightly weaker, associations were observed with waist circumference. We also found increases in fT3 levels with every 1-quartile increase in BMI (1.0% in men and 1.3% in women) and waist circumference (1.2% in men and 1.2% in women). No associations were observed with fT4. Conclusions Our results provide support that BMI and waist circumference are positively associated with levels of serum TSH and f T3 but not fT4 among euthyroid adults. Longitudinal studies are needed to define the temporality of these associations and their potential health implications.